PsycEXTRA Dataset 2007
DOI: 10.1037/e660632007-001
|View full text |Cite
|
Sign up to set email alerts
|

Families Under Stress: An Assessment of Data, Theory, and Research on Marriage and Divorce in the Military

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
269
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(280 citation statements)
references
References 135 publications
(194 reference statements)
5
269
4
2
Order By: Relevance
“…Research indicates that the military environment protects families from the stresses that often lead to divorce and that veterans' marriages become less stable once they leave the supportive military setting. 30,31 …”
Section: Family Confl Ictmentioning
confidence: 99%
“…Research indicates that the military environment protects families from the stresses that often lead to divorce and that veterans' marriages become less stable once they leave the supportive military setting. 30,31 …”
Section: Family Confl Ictmentioning
confidence: 99%
“…Although Karney and Crown found military couples were initially no more likely to divorce than they had been prior to the start of OEF (Karney and Crown 2007), later data showed that among sailors and marines, frequency and length of deployments were associated with higher divorce rates (Arenstein 2011).…”
Section: Current Eramentioning
confidence: 99%
“…A limitation is that the results are from the military personnel's perspective only. Relying on one member of the partnership may give a biased view becasue couples often perceive their relationship differently (Karney & Crown, 2007). The data are cross-sectional; therefore, causation cannot be inferred.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…This study, like much of the U.S. research, did not, however, investigate factors associated with relationship satisfaction and quality. As Karney and Crown (2007) suggest, to look purely at relationship stability is likely to be misleading and limited when evaluating the relationships of military personnel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation